Effects of volcanic eruptions on the mental health of exposed populations: a systematic review - Mendoza, Danae A.; Reales, José M.; Ballesteros, Soledad (Frontiers in Public Health, 2024)
IntroductionMillions of people living in volcanic environments are at risk of experiencing volcanic eruptions, a natural disaster. This systematic review aimed to collect empirical evidence of the effects of volcanic eruptions on the mental health of the exposed populations.MethodsFollowing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we conducted systematic searches on Scopus, PubMed, PsycINFO, Medline, and Web of Science (WoS) databases.ResultsA total of 17,044 articles were screened. Of these, 24 articles met the inclusion criteria and data were extracted. Twenty-one articles investigated psychological disorders, two articles studied emotions and their relationships with certain environmental factors, and one article explored cognitive functions in the exposed populations. These studies showed that highly exposed populations were more vulnerable to develop long-lasting psychological disorders than less exposed populations.ConclusionThe negative influence of experiencing volcanic activity on mental health was confirmed. Clearly, there is a need for more research to improve the mental health of the populations highly exposed to volcanic eruptions. Recommendations for future research are also included.